2015
DOI: 10.1039/c5nr04126k
|View full text |Cite
|
Sign up to set email alerts
|

Vanadium-based nanostructure materials for secondary lithium battery applications

Abstract: Vanadium-based materials, such as V2O5, LiV3O8, VO2(B) and Li3V2(PO4)3 are compounds that share the characteristic of intercalation chemistry. Their layered or open frameworks allow facile ion movement through the interspaces, making them promising cathodes for LIB applications. To bypass bottlenecks occurring in the electrochemical performances of vanadium-based cathodes that derive from their intrinsic low electrical conductivity and ion diffusion coefficients, nano-engineering strategies have been implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(71 citation statements)
references
References 122 publications
1
70
0
Order By: Relevance
“…As show in Fig. 6f, “W” shape curves of both samples are indicative of the characteristics of Li + intercalation-host materials53. The calculated diffusion coefficients of 3D V 2 O 5 /RGO/CNT are higher than those of 2D V 2 O 5 /RGO on the whole process, implying a favorable Li + diffusivity in the ternary composite.…”
Section: Resultsmentioning
confidence: 74%
“…As show in Fig. 6f, “W” shape curves of both samples are indicative of the characteristics of Li + intercalation-host materials53. The calculated diffusion coefficients of 3D V 2 O 5 /RGO/CNT are higher than those of 2D V 2 O 5 /RGO on the whole process, implying a favorable Li + diffusivity in the ternary composite.…”
Section: Resultsmentioning
confidence: 74%
“…2, Fig. 3) have shown that this material exhibits good electrochemical performance comparable to polycrystalline, xerogel or thin film V 2 O 5 -related systems [24]. It means that the change of the microstructure and a substantial increase in the electrical conductivity have not affected its ability to insert/deinsert lithium.…”
Section: V 2 O 5 ·10p 2 O 5 Glasses/nanomaterialsmentioning
confidence: 95%
“…Taking into account this correlation we have postulated that the conductivity enhancement is caused mainly by the presence of interfacial regions around newly formed nanograins. The defective nature of such interfaces can provide good conditions for small polaron hopping, which is a main electronic transport mechanism in systems like V 2 O 5 [20,21], LiFePO 4 [22] or Li 3 V 2 (PO 4 ) 3 [23,24].…”
Section: Introductionmentioning
confidence: 99%
“…At more than two Li + insertion, irreversible transformation of γ-LixV2O5 to rocksalt type ω-LixV2O5 (2 < x < 3) phase occurs. 24 Such phase transition processes induce large lattice strains due to coexistence of different phases within single particles. The lattice mismatch-induced mechanical strain can cause irreversible structural damage resulting in poor battery lifetime and irreversible capacity loss.…”
Section: Introductionmentioning
confidence: 99%